Turkish State Family Law: History Reform, Legislation, and Legal Materials - Doli Witro; Ali Hamzah; Ike Yulisa; Mhd Rasidin; Syamsarina Syamsarina; Hainadri Hainadri (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2020)
Historically, efforts to reform Family Law in parts of the Islamic world began to be realized in the late 19th century AD. The reality of Islamic legal reforms carried out in Islamic countries in North Africa, the Middle East, Central Asia, and Southeast Asia gave rise to unprecedented changes in the last century. These changes occur both in the justice system and in the system applied. Changes to family law were first carried out by Turkey, then followed by Lebanon in 1919, Jordan in 1951, and Syria in 1953. Muslim countries in the world, in their context with the renewal of family law, are divided into three categories. First, an Islamic state that does not carry out any renewal and still enforces family law as stipulated in the books of fiqh. Secondly, an Islamic state that has completely abandoned Islamic family law and adopted European civil law. Third, countries that are trying to enforce Islamic family law but after making reforms here and there. This paper tries to discuss one of the reforms carried out by one Muslim country, namely Turkey, which is related to the reformation (reform) of family law that starts from the history of reform, legislation, renewal, and legal material. The author chose Turkey because it is the first Muslim country to make changes to family law.